The well-known hadith, "Every matter of significance does not begin with the name of God, the Compassionate, the Merciful, it is cut off or amputated" in the nine books - Khairul Umam (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2020)
This study aims to discuss criticism of the hadith about practice which is interrupted without basmalah. The focus of this study is on the aspect of tracing the existence of these hadiths in the kutub tis'ah as well as studying the hadith criticism. This study is a literature study with a descriptive data presentation pattern. The data sources used include the book Mu'jam Mufahros li Alfadz al-Hdits, Tadzhib al-Kamal, and so on. Apart from the purpose of starting all good deeds by chanting the name of Allah, that some differences of opinion about basmalah often occur, giving birth to debates among the people such as whether to start the recitation of fatihah in prayer with basmalah or not, whether basmalah is a verse from surah alfatihah or not, is basmalah included verse of every letter in the Koran or not. The stages of the study carried out were performing hadith takhrij using the alfadz method. Then the hadith that has been reviewed, a ranji sanad is made to criticize the hadith. The findings in this paper indicate that the hadith with the matan redaction “كل امر ذي بال لا يبدأ ببسم الله الرحمن الرحيم فهو أقطع أو أبترnot in the kutub tis'ah. However, the redaction found in several main books of the hadith readكل أمر ذي بال لا يبدأ فيه بالحمد أقطع In terms of hadith criticism, that this hadith is weak because one of the narrators is disabled. تهدف هذه الدراسة إلى مناقشة نقد الحديث "كل أمر ذي بال لا يبدأ ببسم الله الرحمن الرحيم فهو أقطع أو أبتر". وتركز على متابعة وجود ذلك الحديث في الكتب التسعة وكذلك دراسة نقد الحديث. هذه الدراسة هي دراسة مكتبية ويكون عرض بياناتها وصفيا. وتشمل مصادر البيانات المستخدمة المعجم المفهرس لألفاظ الحديث، تذهيب الكمال وغيرهما. وبغض النظر عن مشروعية بدء كل الأعمال الصالحة بذكر اسم الله، قد حدث اختلاف الآراء حول البسملة، بحيث تلد مناظرات بين الناس مثل هل تلزم قراءة البسملة قبل الفاتحة في الصلاة أم لا؟، هل البسملة من أيات الفاتحة أم لا؟، أو هل البسملة من فاتحة كل سور في القرآن الكريم أم لا؟. ومن خطوات هذه الدراسة هي القيام بتخريج الحديث بطريقة الألفاظ، ثم رسم شجرة الأسانيد لأجل نقد الحديث. أظهرت نتائج هذه الدراسة أن الحديث بالمتن "كل أمر ذي بال لا يبدأ ببسم الله الرحمن الرحيم فهو أقطع أو أبتر" لا برد فب الكتب التسعة. ولكن الوارد في بعض أمهات كتب الحديث هو"كل أمر ذي بال لا يبدأ فيه بالحمد أقطع". وفي نقد الحديث، أن هذا الحديث ضعيف لأن في أحد رواته عيب.